Niraparib and Advanced Ovarian Cancer: A Beacon in the Non-BRCA Mutated Setting - Mauro Francesco Pio Maiorano; Brigida Anna Maiorano; Annalucia Biancofiore; Gennaro Cormio; Evaristo Maiello (MDPI AG, 2023)
Ovarian cancer (OC) is the eighth most common cancer among the female population and the most lethal of all the female reproductive system malignancies. Poly (ADP-ribose) polymerase inhibitors (PARPis) have reshaped the treatment scenario of metastatic OC in the maintenance setting post platinum-based chemotherapy. Niraparib is the first Food and Drug Administration (FDA)- and European Medical Agency (EMA)-approved PARPi as maintenance therapy for platinum-sensitive OC, regardless of BReast CAncer gene (BRCA) status, in first-line patients, with a recent restriction to germline BRCA mutations in second-line patients. In this review, we comprehensively summarized the pharmacological properties of niraparib, alongside the efficacy and safety data of the main trials leading to the current approvals, and discussed the future development of this agent.